Estimation of stability of hospital liiquid steril pharmaceutical preparations - Jovović Marija (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Appropriate stability of medicines prepared in hospital conditions should be provided in order to ensure that medicines has suitable quality, safety and terapeutical efficiency. A stability study, based on a certain protocol, must be done for the medicine made in the pharmaceutical conditions to confirm its stability. The results of the study must be precise and reliable, and they must provide enough information on the stability of the product made in the pharmaceutical conditions. The elementary causes of medicine instability, as well as the description of the protocol for examining the stability of the medicines made in pharmaceutical conditions will be given in this research. A stability study of sterile concentrated solution of natrii chloridi, which contains Na+ 1,71 molL-1 i Cl- 1,71 molL-1.will be shown as an example. Stability study was perfomred on three consecutive batches of medicines and on the basis of the obtained results conclusion about drug stability was made.